Notes on Early Land Plants Today. 7. Transfer of Jubulopsis novae-zelandiae to Lepidolaena - Von Konrat, Matt; Söderström, Lars; Hagborg, Anders (Phytotaxa, 2012)
Jubulopsis novae-zelandiae was described by Hodgson et Arnell (Hodgson 1965) as a Jubula Dumortier (1835) species and its position has been questioned. It was transferred to Neohattoria Kamimura (1962) already the year after and later placed in the monotypic genus Jubulopsis Schuster (1970). He-Nygrén et al. (2004, 2006) have shown that it is nested within Lepidolaena Dumortier 1835), but the formal transfer has not yet been made.